Uncertainty, Control, and Karl Polanyi's Protective Response. Issue 2 (3rd April 2018) - Zalewski, David A.
Abstract: Post-Keynesian institutionalist economists like Wallace Peterson and John Kenneth Galbraith recognized that the impact of uncertainty on economic wellbeing depends in part on the degree of control people have over the sources and consequences of it. Given the inability of government and other large institutions to reduce uncertainty or to provide citizens with the ability to manage it, mediating structures are considered as an alternative means of promoting economic security. The article concludes by describing and evaluating several of these alternatives.